Should single-incision laparoscopic appendectomy be the new standard for pediatric appendicitis? - Paul Chia-Yu Chang; Sheng-Chieh Lin; Yih-Cherng Duh; Hsuan Huang; Yu-Wei Fu; Yao-Jen Hsu; Chin-Hung Wei (Pediatrics and Neonatology)
Background: To compare single-incision laparoscopic appendectomy (SILA) with conventional (CLA) and transumbilical laparoscopic appendectomy (TULA). Methods: This is a retrospective cohort study. Patients were divided into three groups, SILA, CLA, and TULA. SILA was defined as performing appendectomy extracorporeally or intracorporeally by using a glove-port incorporated with 3 trocars. TULA was defined as exteriorizing appendix and performing extracorporeal appendectomy by using an operative telescope. Statistical analysis was conducted in patients with simple (SA) and complicated appendicitis (CA), respectively. Results: A total of 315 patients were enrolled, including 161 in SILA, 105 in CLA, and 49 in TULA. Demographic data were similar. In patients with simple appendicitis, operation time of SILA was shorter than CLA but longer than TULA (62.8 ± 22.5 vs. 82.2 ± 24.3 and 51.6 ± 22.3 min, p < 0.01). SILA had shorter hospital stay than CLA, and similar to TULA (56.1 ± 20.4 vs. 71.5 ± 37.8 and 56.9 ± 19.0 h, p < 0.01). In patients with complicated appendicitis, SILA had shorter operation time than CLA, but a similar time to TULA (80.9 ± 22.4 vs. 105.7 ± 28.8 and 82.5 ± 31.2 min, p < 0.01). Conversion to open surgery was not required in all groups. The rates of complications, such as wound infection, intraabdominal abscess and adhesion ileus, were similar. SILA required fewer additional ports than TULA in both simple and complicated appendicitis (1.1% vs. 13.5%, and 9.6% vs. 41.7%, p < 0.01). Conclusion: SILA has the advantages of shorter operation time and hospital stay over CLA as well as a lower rate of additional ports than TULA.